Microstructure Evolution of Grade X100 Pipeline under Plastic Deformation Condition - Lihua Qi; Long Yang; Jing Niu; Yaorong Feng; Jianxun Zhang (Advances in Materials Science and Engineering)
The effects of plastic deformation on the microstructure evolution of grade X100 pipeline were investigated by SEM, TEM and EBSD tests. The result shows that quasipolygon ferrite deforms firstly under plastic strain initial stage, then both acicular ferrite and granular bainite change remarkably with the value of plastic strain increase. When the tension stress reaches the tensile strength, microcracks nucleate around the inclusion and M/A constitute, expand with the plastic deformation increases, and finally cracks connection causes the crack penetration until the expiration. Furthermore, the microscopic orientation concentrates in {110} 〈111〉 direction before the deformation, while crystal orientation in {110} and {112} direction enhanced after the deformation.